DAMPAK KUALITAS PELAYANAN JASA PENDIDIKAN TERHADAP KEPUASAN PESERTA DIDIK PADA JURUSAN KESELAMATAN PENERBANGAN DI STPI-CURUG - IRWAN FAIZAL (Langit Biru: Jurnal Ilmiah Aviasi, 2012)
The purpose of education is to develop the potential of students to be man who is faithful and devoted to God Almighty, glorious, healthy, knowledgeable, skilled, creative, independent and become citizens of a democratic and accountable. To improve competitiveness and achieve educational goals, educational institutions are required constantly improve educational services. Competition educational institutions not only from physical factors, but is also determined by a system service capable of providing satisfaction to students. This research aims to determine how the effect of the quality of educational services to customer satisfaction and the extent of educational services provided by the Department of Flight Safety, ICAI Curug. The analysis technique used is descriptive method of quantitative analysis that presents the facts about what it is going to systematically about the state perceived by the object of research. The analysis indicates that service quality had a positive effect on customer satisfaction and services provide by institution generally is good.